The Effects of Massage Therapy on Sport and Exercise Performance: A Systematic Review - Miloš Dakić; Lazar Toskić; Vladimir Ilić; Saša Đurić; Milivoj Dopsaj; Jožef Šimenko (MDPI AG, 2023)
Background: A massage is a tool that is frequently used in sports and exercise in general for recovery and increased performance. In this review paper, we aimed to search and systemize current literature findings relating to massages' effects on sports and exercise performance concerning its effects on motor abilities and neurophysiological and psychological mechanisms. Methods: The review has been written following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) guidelines. One hundred and fourteen articles were included in this review. Results: The data revealed that massages, in general, do not affect motor abilities, except flexibility. However, several studies demonstrated that positive muscle force and strength changed 48 h after the massage was given. Concerning neurophysiological parameters, the massage did not change blood lactate clearance, muscle blood flow, muscle temperature, or activation. However, many studies indicate pain reduction and delayed onset muscle soreness, which are probably correlated with the reduction of the level of creatine kinase enzyme and psychological mechanisms. In addition, the massage treatment led to a decrease in depression, stress, anxiety, and the perception of fatigue and an increase in mood, relaxation, and the perception of recovery. Conclusion: The direct usage of massages just for gaining results in sport and exercise performance seems questionable. However, it is indirectly connected to performance as an important tool when an athlete should stay focused and relaxed during competition or training and recover after them.